EFFECT OF PREOPERATIVE INTRAVENOUS STERIODS ON SEROMA FORMATION AFTER MODIFIED RADICAL MASTECTOMY - Khan, Maryam Alam (Journal of Ayub Medical College Abbottabad, 2017)
Background: With the steep increase in breast cancer incidence globally and regionally, there has been a trend toward reducing patient morbidity by meticulous surgical techniques to obviate complications like seroma formation; use to pre-operative steroids seems to be convenient, cost effective and shows promising results in trials. Methods: This randomized clinical trial was conducted at Surgical Department of Khyber Teaching Hospital Peshawar, from January 2012 to April 2014 on 65 patients randomly allocated to Group A and Group B using lottery method. Group A underwent MRM+AD in the conventional manner while Group B received a 120 mg of injection Depomedrol intravenously 1 hour before the surgery. The two were compared in terms of total drainage, days of drainage, wound complications and incidence of seroma. Data was entered and analysed using statistical program SPSS-21. Results: The mean age in group A was 34.2±10.1 years and B was 32.3±9.1 years. The mean drainage in intervention group was significantly reduced as compared to control group (755.4±65ml vs 928.3±102.5). Total drainage days were reduced (6.5±1.6 days vs 10.2±2.2 days) and incidence of seroma was also reduced (A=18.75% vs B=6.06%). However, three patients in group B had wound infection. Conclusions: Seroma formation is the most common complication of Mastectomy and among the methods used to reduce its incidence, steroid administration seems to be the most cost effective and shows promising results. Keywords: Mastectomy; Modified Radical Mastectomy; Methylprednisolone; Seroma Formation